In vivo Waveguide elastography: Effects of neurodegeneration in patients with amyotrophic lateral sclerosis - Romano, Anthony; Prokscha, Torben; Meyer, Thomas; Hirsch, Sebastian; Braun, Juergen; Scheel, Michael; Sack, Ingolf; Guo, Jing (Magnetic Resonance in Medicine, 2014)
Purpose: Waveguide elastography (WGE) combines magnetic resonance elastography (MRE), diffusion tensor imaging (DTI), and anisotropic inversions for a determination of the elastic properties of white matter. Previously, the method evaluated the anisotropic elastic properties of the corticospinal tracts (CSTs) of healthy volunteers. Here, the sensitivity of WGE is tested for the detection of pathologic changes in a cohort of patients with Amyotrophic Lateral Sclerosis (ALS).
CRIS-Team Scopus Importer:2022-08-03
Keywords: Amyotrophic lateral sclerosis; Anisotropic inversions; Diffusion tensor imaging; Magnetic resonance elastography; Waveguide elastography; White matter tracts